Parenting and Ninth Graders' Self‐Efficacy and Relational Self‐Esteem in Latino Immigrant Families. (March 2015) - Yomtov, Dani; Plunkett, Scott W.; Sands, Tovah; Reid, Alex
<x xml:space="preserve">Abstract</x> The purpose of this study was to examine whether Latino adolescents' perceptions of maternal and paternal behaviors (support, psychological control) were related to their general self‐efficacy and relational self‐esteem. Self‐report surveys were collected from 662 Latino ninth graders from three public high schools in Los Angeles. The results were consistent with the looking glass self and self‐efficacy theory. The results showed that perceived supportive behaviors from mothers and fathers were significantly and positively related to boys' and girls' general self‐efficacy and relational self‐esteem, while perceived psychologically controlling behaviors from mothers and fathers were significantly and negatively related to general self‐efficacy. Extension educators and human service professionals serving Latino families should encourage supportive parenting behaviors, caution against the use of psychological control, help Latino youth recognize supportive behaviors by parents, and teach Latino youth strategies to buffer themselves from the impact of parents' psychological control.